The Impact of Financial Development on Human Capital: Evidence From Emerging Market Economies - KILIÇ, Cüneyt; Ozcan, Burcu (International Journal of Economics and Financial Issues, 2018)
This study aims to analyze the effect of financial development on human capital in emerging market economies over the years 1990-2015. To this aim, two different panel data models including different proxies for human capital are constructed. Results from both models indicate that financial development positively affects the human capital level of emerging market economies. Besides, some causality linkages are obtained between financial development and human capital indicators. Based on the findings of the study, some important policy implications could be suggested. Keyword: Financial development, Human capital, Economic growth, Panel data analysis, Emerging market economies. JEL Classifications: E44, G20, J24, O16